The Effect of Fraud Accounting And Characteristics of Corruption Criminal Acts on Prosecutors' Demands With Behavioral Judgement as a Moderating Variable (Case Study of The Bireuen District Prosecutor's Office) - Pratikno, Dedi Agus; Maisyarah, Renny (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the influence of fraud accounting (X1) and corruption crime characteristics (X2) on the prosecutor's demand (Y), and to examine the moderating role of behavioral judgement (Z). The research is motivated by findings that the criminal demands filed by prosecutors at the Bireuen District Attorney’s Office do not always correspond with the magnitude of state financial losses resulting from corruption. While fraud accounting findings should serve as an indicator to aggravate the sentence demand, they are occasionally not accommodated proportionally in the prosecution demands. The research employed an associative and cross-sectional approach, utilizing multiple linear regression and moderation analysis (interaction term). The sample consisted of 92 prosecutors who had prepared prosecution demands for corruption cases at the Bireuen District Attorney's Office during the 2020–2025 period. The results show that fraud accounting (X1) and corruption crime characteristics (X2) simultaneously have a significant influence on the prosecutor's demand (Y) by 82.0%. Partially, both independent variables demonstrated a positive and significant effect on the prosecutor's demand. Furthermore, behavioral judgement was proven to strengthen (moderate) the influence of fraud accounting on the prosecutor's demand. It also strengthens the influence of corruption crime characteristics on the prosecutor's demand. This finding reinforces the view that prosecution decisions are not solely based on objective accounting data but also on the integrity, rationality, and justice practiced by the prosecutor (behavioral judgement).